1999
DOI: 10.1038/sj.bjp.0702632
|View full text |Cite
|
Sign up to set email alerts
|

RS‐127445: a selective, high affinity, orally bioavailable 5‐HT2B receptor antagonist

Abstract: to de®ne precisely the role of 5-HT 2B receptors in normal and disease processes have been hindered by the absence of selective antagonists. To address this de®ciency, we developed a series of naphthylpyrimidines as potentially useful 5-HT 2B receptor antagonists. 2 RS-127445 (2-amino-4-(4-¯uoronaphth-1-yl)-6-isopropylpyrimidine) was found to have nanomolar a nity for the 5-HT 2B receptor (pK i =9.5+0.1) and 1,000 fold selectivity for this receptor as compared to numerous other receptor and ion channel binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 21 publications
5
98
1
1
Order By: Relevance
“…RS-127445 was found to have subnanomolar affinity for the 5-HT 2B receptor (pK i ϭ 9.5 Ϯ 0.1) and at least 1000-fold selectivity for this receptor compared with numerous other receptors and monoamine uptake sites (Bonhaus et al, 1999). Some of these receptors are of special interest in MDMA-induced locomotion, especially 5-HT 2A , 5-HT 2C , and 5-HT 1B receptors, but also 5-HT and DA transporters (Bankson and Cunningham, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RS-127445 was found to have subnanomolar affinity for the 5-HT 2B receptor (pK i ϭ 9.5 Ϯ 0.1) and at least 1000-fold selectivity for this receptor compared with numerous other receptors and monoamine uptake sites (Bonhaus et al, 1999). Some of these receptors are of special interest in MDMA-induced locomotion, especially 5-HT 2A , 5-HT 2C , and 5-HT 1B receptors, but also 5-HT and DA transporters (Bankson and Cunningham, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…MDMA (Sigma-Aldrich, Saint-Quentin Fallavier, France) was dissolved in 0.9% (w/v) NaCl solution (saline); RS127445 (Bonhaus et al, 1999) was kindly provided by Roche Bioscience (Indianapolis, IN) and slowly dissolved in saline solution. BW723C86 (Sigma-Aldrich) was dissolved in saline solution.…”
Section: Animals 5-ht 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple and sensitive in vitro assay for acute effects at the 5-HT 2B receptor is the rat gastric fundus contraction assay, first described by (Sir) John Vane. Here we found 5-APB to cause contraction of the rat fundus, an effect antagonised by the specific 5-HT 2B receptor antagonist RS127445 (Bonhaus et al, 1999). We also found 5-HT and MDMA to cause contraction of the fundus, with 5-APB having a greater efficacy than MDMA, a drug already linked to valvulopathies (Bhattacharyya et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 57%
“…In comparison to 5-HT, 5-APB and MDMA appeared to be partial agonists as the maximal responses to these drugs were lower than 5-HT itself. The concentration-effect curves for all three agonists were significantly right-shifted by the 5-HT 2B antagonist RS 127445 (1 µM; Bonhaus et al, 1999); the results for 5-APB are shown in figure 4C.…”
Section: Contractions In Rat Fundusmentioning
confidence: 88%